Climate, soil and plant functional types as drivers of global fine‐root trait variation. (10th April 2017) - Freschet, Grégoire T.; Valverde‐Barrantes, Oscar J.; Tucker, Caroline M.; Craine, Joseph M.; McCormack, M. Luke; Violle, Cyrille; Fort, Florian; Blackwood, Christopher B.; Urban‐Mead, Katherine R.; Iversen, Colleen M.; Bonis, Anne; Comas, Louise H.; et al.
Summary: Ecosystem functioning relies heavily on below‐ground processes, which are largely regulated by plant fine‐roots and their functional traits. However, our knowledge of fine‐root trait distribution relies to date on local‐ and regional‐scale studies with limited numbers of species, growth forms and environmental variation. We compiled a world‐wide fine‐root trait dataset, featuring 1115 species from contrasting climatic areas, phylogeny and growth forms to test a series of hypotheses pertaining to the influence of plant functional types, soil and climate variables, and the degree of manipulation of plant growing conditions on species fine‐root trait variation. Most particularly, we tested the competing hypotheses that fine‐root traits typical of faster return on investment would be most strongly associated with conditions of limiting versus favourable soil resource availability. We accounted for both data source and species phylogenetic relatedness. We demonstrate that: (i) Climate conditions promoting soil fertility relate negatively to fine‐root traits favouring fast soil resource acquisition, with a particularly strong positive effect of temperature on fine‐root diameter and negative effect on specific root length (SRL), and a negative effect of rainfall on root nitrogen concentration; (ii) Soil bulk density strongly influences species fine‐root morphology, by favouring thicker, denser fine‐roots; (iii) Fine‐roots from herbaceous species are on average finer and have higher SRL than those of woody species, and N2 ‐fixing capacity positively relates to root nitrogen; and (iv) Plants growing in pots have higher SRL than those grown in the field. Synthesis . This study reveals both the large variation in fine‐root traits encountered globally and the relevance of several key plant functional types and soil and climate variables for explaining a substantial part of this variation. Climate, particularly temperature, and plant functional types were the two strongest predictors of fine‐root trait variation. High trait variation occurred at local scales, suggesting that wide‐ranging below‐ground resource economics strategies are viable within most climatic areas and soil conditions. Abstract : The long and complex evolution of plant roots, and their occurrence in multiple environmental conditions, have shaped a large diversity of forms and functions among plant species. Here we gathered a worldwide fine‐root trait dataset and demonstrated that climate and plant functional types were the two strongest predictors of fine‐root trait variation. Particularly, climate conditions promoting soil fertility related negatively to fine‐root traits favouring fast soil resource acquisition, with a particularly strong positive effect of temperature on fine‐root diameter and negative effect on specific root length, and a negative effect of rainfall on root nitrogen.